Yield Decline and Resistance Development in Sucking Pests of Cotton in the Context of Unwise Spraying Techniques - Saleem Ashraf; Khalid Mahmood Ch.; Ijaz Ashraf (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Over 100 countries are producing cotton, which provides raw materials to the industry and employment opportunities for the people. Limiting the cost of production, conserving the ecosystem, and improving the cotton yield are key ingredients of sustainable cotton production. The inception of transgenic cotton (Bt varieties) improved yields, curtailed pesticide uses and promoted environmental safety. Over the years, Bt varieties of cotton have lost resistance against bollworms, and yield is declining. Unwise application of pesticides is associated with the development of resistance to sucking pests of cotton. The present review was conducted to undertake (i) the background of cotton production in the world, (ii) varietal development in cotton, (iii) problems (increasing susceptibility) in Bt varieties (iv) reliance on pesticides, and (v) myths of pesticides applications followed by pesticides knowledge among farmers. The cotton varieties which are resistant against sucking pests should be introduced. In addition, the promotion of biopesticides and fostering the adoption of Integrated Pest Management Approaches could be effective for the management of sucking pests. Farmers must be trained in site-specific and accurate spraying techniques by agricultural extension and plant protection departments. Accurate spraying techniques will not only improve pest control but also help in curtailing the environmental pollution being caused by the excessive use of pesticides in cotton.